Direct Ink Writing Based 4D Printing of Materials and Their Applications. Issue 16 (29th June 2020) - Wan, Xue; Luo, Lan; Liu, Yanju; Leng, Jinsong
Abstract: 4D printing has attracted academic interest in the recent years because it endows static printed structures with dynamic properties with the change of time. The shapes, functionalities, or properties of the 4D printed objects could alter under various stimuli such as heat, light, electric, and magnetic field. Briefly, 4D printing is the development of 3D printing with the fourth dimension of time. Among the fabrication techniques that have been employed for 4D printing, the direct ink writing technique shows superiority due to its open source for various types of materials. Herein, the state‐of‐the‐art achievements about the topic of 4D printing through direct ink writing are summarized. The types of materials, printing strategies, actuated methods, and their potential applications are discussed in detail. To date, most efforts have been devoted to shape‐shifting materials, including shape memory polymers, hydrogels, and liquid crystal elastomers, showing great prospects in areas ranging from the biomedical field to robotics. Finally, the current challenges and outlook toward 4D printing based on direct ink writing are also pointed out to leave open a significant space for future innovation. Abstract : 4D printing has attracted wide attention due to its potential to extend the design space beyond complex geometries with the change of time. Recent achievements in 4D printing based on the direct ink writing technique are reviewed in detail, including types of materials, their functionalities, and applications. Current challenges, future developing trends, and directions are also presented.